A case report on late presentation of occult dural lesions - Timothy Cochrane; Gurpreet Singh Ranger (Babol University of Medical Sciences, 2017)
Background: Occult dural injuries are rare and can occur as a result of major or minor head injury. These injuries usually manifest with cerebrospinal fluid rhinorrhea alone, or with meningitis and cerebral abscess, sometimes many years after the original injury. Case presentation: We present a case of occult dural injury with endocranial complications which occurred in a 34 year old man, with a history of head injury forty-three years ago. The patient presented with a triad of findings; meningitis, CSF rhinorrhoea and pneumocephalus. He was managed conservatively with intravenous antibiotics and observation and made a full recovery. The presence of acute endocranial symptoms and particularly these three findings in a patient with a previous history of head injury, no matter how long it had been should raise suspicion of the presence of an occult dural injury. Conclusion: It need to retain a high index of suspicion for occult dural injury in patients who present with endocranial symptoms of unknown origin, especially if there is a previous history of head injury.